Effect of Work Stress on the Productivity of Shift Workers in Production Department at Pt.x Makassar City - Herlin Manga Lambo; Rafael Djajakusli; Masyitha Muis; Atjo Wahyu; Apik Indarty Moedjiono; Darmawansyah (Institute of Medico-legal Publications Pvt Ltd, 2022)
Productivity can be defined as worker’s performance in terms of quantity, quality and timeliness. Thereare several factors that can affect productivity. This study aims to determine the effect of monotonyand work stress on production department’s shift workers at PT. X wirh age, sex, years of service andquality of sleep as a control variables.This study was an analytic observational study with cross sectional design. The number of respondentswas 49 people which were determined using purposive sampling technique. Data were obtained usingonline questionnaires. Chi square was used for bivariate data analysis and multiple logistic regressionfor multivariate data analysis.From the results of bivariate data analysis, it was found that work stress had an effect on productivitywith a value of p = 0.001 (<0.05). For the analysis of work stress based on age, it affected older workerswith a value of p = 0.004, while based on gender, it affected the female workers with a value of p =0.001, based on years service, it had effect on long service years with a value of p = 0.018 and basedon sleep quality, it affected on poor sleep quality with a value of p = 0.003. The results of multivariateanalysis showed that work stress affected the productivity with a value of p = 0.001 (p <0.05) withgender and sleep quality as variable controls. It was suggested for workers to maximize the rest timeafter serviced a night shift in order to restore their physical condition and for company leaders toestablish good communication towards workers in order to find out critics or suggestion related to thejob.